Foreign Cooperation as an Institution of Regional Development: an Analysis of Implementation in West Java Provincial Government - Bedi Budiman; M. Rizky Ganda Hutama; Iwan Gunawan; Yulinar Fachriny Ayuba (UNIVERSITAS PAKUAN, 2026)
Global developments and the decentralization of governmental authority have encouraged regional governments to utilise international cooperation as an instrument for regional development through the practice of paradiplomacy. This study aims to analyse the implementation and contribution of the international cooperation undertaken by the West Java Provincial Government in supporting regional development, while identifying the factors that facilitate and constrain its implementation. The study employs a descriptive qualitative approach. Data were collected through document analysis, a review of relevant literature, and an in depth interview with a practitioner from the Bureau of Government and Regional Autonomy of the West Java Provincial Government. The analytical framework integrates the policy implementation models of Van Meter and Van Horn and Mazmanian and Sabatier within the perspective of multi level governance. The findings indicate that West Java's international cooperation has contributed to regional development in the economic, employment, and cultural sectors. However, its long term effectiveness depends on the comprehensive fulfilment of the Six Governance Conditions, with institutional capacity and intergovernmental coordination remaining the principal challenges to effective implementation.